THE ABSENCE OF A MAXIMUM LEGAL TERM FOR PREVENTIVE DETENTION AND THE MAINTENANCE OF PUNITIVE POWER (Reflection and Critique Law Magazine, 2025)
The present work aims to study the absence of a legal term for the duration of preventive detention in Brazil through a historical and contemporary analysis showing the punitive passion that keeps people incarcerated indefinitely in Brazil. To fulfill this objective, we will relate some concepts related to criminal precautionary measures, also analyzing the guiding principles of criminal proceedings, some criminological aspects related to the subject and data referring to provisional incarceration in Brazil, aiming to offer epistemological references that contribute to the development of the subject. Also, by consulting foreign diplomas, a comparison will be made with Brazilian legislation. In the end, after presenting the problem, it will be necessary to stipulate deadlines for the application of the measure.